Wind and Trees: Surveys of Tree Damage in the Florida Panhandle after Hurricanes Erin and Opal - Mary L. Duryea (EDIS)
This document summarizes the results of surveys conducted after Hurricanes Erin and Opal in 1995, which assessed tree damage in the Florida Panhandle. It ranks the wind resistance of various tree species, highlighting that species like dogwood, live oak, and sabal palm showed high wind resistance, while species like sand pine and Carolina laurelcherry were less resistant. The findings emphasize the importance of selecting wind-resistant trees for hurricane-prone areas and suggest that proper tree care and maintenance can mitigate damage. First published: May, 1997.